2007
DOI: 10.1007/s10531-006-6733-1
|View full text |Cite
|
Sign up to set email alerts
|

Is vascular plant species diversity a predictor of bryophyte species diversity in Mediterranean forests?

Abstract: This study aimed to (i) investigate the congruence among the species composition and diversity of bryophytes and vascular plants in forests; (ii) test if site prioritization for conservation aims by the maximization of the pooled number of vascular plant species is effective to maximize the pooled number of bryophyte species. The study was performed in six forests in Tuscany, Italy. Four-hundred and twenty vascular plant species (61 of which were woody) and 128 bryophyte species were recorded in 109 plots. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 35 publications
(48 reference statements)
2
21
1
2
Order By: Relevance
“…Several authors have concluded that rare species sites do not coincide with the biodiversity hotspots of other taxa (Benayas and de la Montaña 2003;Chiarucci et al 2007), rather that the spatial patterns of species richness are determined mainly by more common species (Pearman and Weber 2007). Although we found that common species have lower indicator values in predicting the presence/absence of other orchids than the relatively rare orchids O. insectifera, M. monophyllos, G. conopsea, and D. russowii, these species are not true rarities in the study area.…”
Section: Indicator Value Of Data Layers and Featurescontrasting
confidence: 71%
“…Several authors have concluded that rare species sites do not coincide with the biodiversity hotspots of other taxa (Benayas and de la Montaña 2003;Chiarucci et al 2007), rather that the spatial patterns of species richness are determined mainly by more common species (Pearman and Weber 2007). Although we found that common species have lower indicator values in predicting the presence/absence of other orchids than the relatively rare orchids O. insectifera, M. monophyllos, G. conopsea, and D. russowii, these species are not true rarities in the study area.…”
Section: Indicator Value Of Data Layers and Featurescontrasting
confidence: 71%
“…where I jk is the incidence of species j in plot k, F j is total number of plots containing species j, N is the total number of plots and S k is the number of species in the plot k (Palmer et al 2002;Chiarucci et al 2007). This index ranges from zero (no infrequent species) to one (only infrequent species).…”
Section: Data Analysesmentioning
confidence: 99%
“…In addition, in contrast with subjective sampling designs, random sampling can be applied to infer plant species diversity using one of the numerous sample based methods for estimating total species richness. Rarefaction curves (Sanders 1968) are now a widely used and accepted method for estimating standardized species richness (Gotelli and Colwell 2001;Koellner et al 2004;Williams et al 2007;Chiarucci et al 2007). Comparable measurements of species richness along the coastal dune gradient, which evidence rare and endangered species, can help answering crucial questions for ecosystem management such as which community best contributes to total species diversity or which are the priority habitats to propose for conservation planning.…”
Section: Introductionmentioning
confidence: 99%
“…La protección de un área por su riqueza de plantas vasculares y vertebrados no siempre garantiza la conservación de la diversidad de briofi tas (Hallingbäck y Hodgetts, 2000; Chiarucci et al, 2007). Por el momento, la presencia de las especies señaladas indica la importancia de los BHM de la región terrestre prioritaria Sierra Gorda-Río Moctezuma.…”
Section: Discussionunclassified